Laporan Kasus: Pendekatan Kedokteran Keluarga pada Pasien Perempuan Usia 48 Tahun dengan Hipertensi Grade II di Puskesmas Nisam Aceh Utara - Nurul Razoki Yonianda Panjaitan; Noviana Zara (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Hypertension is one of the most common chronic diseases encountered in primary healthcare and may lead to serious complications if left uncontrolled. This case report aims to describe the management of a 48-year-old female patient with grade II hypertension through a family medicine approach at Nisam Primary Health Center, North Aceh Regency. The patient presented with intermittent headaches for one week, which worsened after physical activity and were accompanied by numbness in both legs. She had a five-year history of hypertension with poor adherence to antihypertensive medication. Physical examination revealed a blood pressure of 165/70 mmHg, leading to a diagnosis of grade II hypertension. Comprehensive management was conducted using patient-centered and family-centered approaches, including education regarding hypertension, lifestyle modification, DASH diet implementation, physical activity, medication adherence, and family support through home visits and family folders. The interventions were expected to improve blood pressure control, prevent complications, and enhance the patient’s quality of life. A family medicine approach plays an important role in comprehensive hypertension management at the primary healthcare level.